Exercise Countermeasures for the Spine in Microgravity - Sayson, Joselito V; Hargens, Alan R (Revista Cubana de Investigaciones Biomédicas, 2019)
Weakness and neuromuscular deconditioning of the anti-gravity spine muscles develop after 6-month missions in space. There is also a high incidence of herniated nucleus pulposus in cervical and lumbar discs with back pain post-flight. Prolonged microgravity reduces the physiological loading forces needed for spine homeostasis and may alter neuromuscular postural reflexes leading to injury upon return to 1G. Nine astronauts were tested using the Biering-Sorensen test to measure spine isometric endurance pre- and post-flight. The results show significant decrements in muscle isometric endurance and correlates with atrophy of the multifidus, erector spinae, quadratus lumborum and psoas, reduced cross-sectional area and functional cross-sectional area with MRI measurements. Current ISS exercise countermeasures appear to be insufficient in mitigating loss of spinal function due to lack of specifically designed exercises to address specific antigravity muscles. Intensity of resistance loading is proposed to be specific to the muscle isoform that needs the most optimal mechanotransduction using adjustable pulley resistance vectors in line or parallel to the target muscle fibre orientations. Pulley apparatus may be in the form of flywheel or pneumatic derived resistance. Since antigravity muscles are predominantly Type I muscle isoform, endurance and stability are the main functional qualities which would require higher repetitions in good form, moderate resistance, and multiple sets. This proposal is intended to define efficient type of spine exercises to counter the maladaptive effects from prolonged spaceflight and lead to accepted countermeasures. Supported by NASA Grants NNXlOAM18G and NNX13AM89G.